2022
DOI: 10.3390/molecules27228033
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Heavy Metals and Organic Micropollutants in Drinking Water Sources in Typical Villages and Towns in Northeast China

Abstract: This study identified and detected the existence of major pollutants in northeast China. As an alpine region and an agricultural base, this region has representative significance in pollution research. We selected 56 samples from drinking water sources of typical villages and towns, focusing on the analysis of heavy metals and organic micropollutants in northeast China. The analysis results showed that Fe and Mn were the main metal elements exceeding the standard. The exceeding rates were 17.9% and 19.6%. Expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In addition, the leaching amount of metal ions in the solution was detected by ICP-MS. The results showed that the leaching amount of Cu 2+ was 0.22 mg/L, much lower than the Chinese Sanitary Standard for Domestic Drinking Water GB 5749-2022 [36]. After five consecutive cycles, the catalysts were analyzed by XRD, and the results are shown in Figure S1.…”
Section: The Recyclability Of Cu/cuo-bcmentioning
confidence: 99%
“…In addition, the leaching amount of metal ions in the solution was detected by ICP-MS. The results showed that the leaching amount of Cu 2+ was 0.22 mg/L, much lower than the Chinese Sanitary Standard for Domestic Drinking Water GB 5749-2022 [36]. After five consecutive cycles, the catalysts were analyzed by XRD, and the results are shown in Figure S1.…”
Section: The Recyclability Of Cu/cuo-bcmentioning
confidence: 99%
“…However, two recent studies conducted in China report the presence of pesticides and flame retardants in the region of Taihu Basin, in which even advanced treatment procedures were inefficient in removing these contaminants (Ren et al, 2020). In the region of northeast China (Heilongjiang, Jilin, and Liaoning provinces), 19 kinds of pesticides, 6 kinds of organophosphates, 2 kinds of phthalates, and 22 kinds of pharmaceutical and personal care product pollutants were found in drinking water samples (Wang et al, 2022).…”
Section: Micropollutants In Domestic Wastewatermentioning
confidence: 99%
“…HQ = HQ oral + HQ dermal (7) HQ oral = CDI oral /Rfd oral (8) HQ dermal = CDI dermal /Rfd dermal ( 9)…”
Section: Health Risk Assessment Modelmentioning
confidence: 99%
“…The pollutants in the water environment have become more complex with the development of technology and the intensification of anthropogenic activities [7]. Among the numerous pollutants, heavy metals have attracted global attention for decades due to their non-biodegradability and their high stability and persistence in either the environment or living organisms [8][9][10].…”
Section: Introductionmentioning
confidence: 99%